Pakeliran Wayang Gambuh "Geseng Alas" - wayan kembalyana swara; I Made Marajaya; Sang Nyoman Gede Adhi Santika (JURNAL DAMAR PEDALANGAN, 2026)
The creation of the Wayang Gambuh performance “Geseng Alas” is grounded in the declining public interest in Balinese puppetry due to the dominance of modern entertainment forms that are more visually appealing and instant. This condition necessitates aesthetic innovation and revitalization strategies without neglecting the philosophical and structural conventions of traditional puppetry. This study aims to describe the creative process and performative structure as a model of tradition-based innovation. A qualitative-descriptive method was employed through participatory observation, literature review, and textual analysis of the pakeliran structure, combined with creative practice exploration at Kakul Mas Art Studio. The findings reveal that the integration of shadow puppetry and Gambuh dance produces a new aesthetic synthesis through intensified dramaturgy, visual exploration, and expanded performative dimensions of the dalang. This innovation not only enriches the artistic idiom of puppetry but also functions as an adaptive revitalization strategy aligned with contemporary audience preferences. The study concludes that this cross-traditional collaborative model contributes significantly to the discourse of puppetry creation as a dynamic artistic practice while reinforcing its socio-cultural function in preserving Balinese heritage.